2018
DOI: 10.1186/s13561-018-0197-3
|View full text |Cite
|
Sign up to set email alerts
|

Real-world cost-effectiveness of cetuximab in the third-line treatment of metastatic colorectal cancer based on patient chart review in the Netherlands

Abstract: ObjectiveTo assess the cost effectiveness of cetuximab in third-line treatment of patients with KRAS wild-type (wt) metastatic colorectal cancer (mCRC) in routine clinical practice compared with best supportive care (BSC).MethodsPatients (n = 287) with KRAS wt mCRC treated with cetuximab or BSC in eight hospitals in the Netherlands between 2009 and 2012 were included in our real-world study. Outcome measures were costs per life-year (LY) and costs per quality-adjusted LY (QALY) gained. A Markov model was devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Owing to the severity of sepsis, a WTP threshold of €80,000/QALY is most likely applicable, although the results will also be analysed using a WTP threshold of €20,000/QALY. Similarly, the high WTP threshold is also used in interventions for metastatic breast, lung, or colorectal cancer, and for bypass surgery or percutaneous coronary intervention [ 31 – 34 ]. In some conditions, the ICUR may however be much higher, as illustrated by an ICUR of €133,527 per QALY gained for chemotherapy treatment (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the severity of sepsis, a WTP threshold of €80,000/QALY is most likely applicable, although the results will also be analysed using a WTP threshold of €20,000/QALY. Similarly, the high WTP threshold is also used in interventions for metastatic breast, lung, or colorectal cancer, and for bypass surgery or percutaneous coronary intervention [ 31 – 34 ]. In some conditions, the ICUR may however be much higher, as illustrated by an ICUR of €133,527 per QALY gained for chemotherapy treatment (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In some conditions, the ICUR may however be much higher, as illustrated by an ICUR of €133,527 per QALY gained for chemotherapy treatment (i.e. cetuximab) vs. best supportive care in metastatic colorectal cancer [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Only 17 studies (33%) reported individual patient data (IPD) as the source of evidence on treatment efficacy, 13 of which used data from randomized trials and four used observational data [47,48,63,77]. Eleven (85%) out of 13 studies that had access to IPD from randomized trials were funded by industry.…”
Section: Sources Of Evidence and Extrapolationmentioning
confidence: 99%
“…the shape and scale parameters of a Weibull distribution) or time-dependent transition probabilities should be accounted for [91]. Of all 22 studies that accounted for uncertainty in time-to-event related parameters, only a few reflected correlation between distribution parameters [30,39,51,52,64,91] or reflected uncertainty in median or mean survival based on which parameters were estimated [32,40,45], whereas others used beta distributions for individual probabilities and hazard ratios [35,46,48,55,69], other distributions [49,67,75,77,81], or provided no information [36,42,56,73]. This indicates a need for increased awareness of the importance of reflecting uncertainty in time-to-event parameters and the appropriate methods to do so.…”
Section: Validation and Analysis Of Modelsmentioning
confidence: 99%
“…Evidently, the different hydrogen-bonding and stacking in G/T and G/A mismatches results in different thermodynamic trends. BRAF V600E mutation testing has demonstrated utility in helping select CRC patients who are considering monoclonal antibody therapy as wild-type BRAF is required for response to anti-EGFR antibodies 23 and improve diagnostic accuracy in thyroid FNA samples. 12,13 In addition, BRAF V600E mutation is connected with sporadic microsatellite instable CRC, but not hereditary non-polyposis colorectal cancer (HNPCC) syndrome.…”
Section: Resultsmentioning
confidence: 99%